Genetic aspects of potato resistance to phytophthorosis - T. S. Frolova; V. A. Cherenko; O. I. Sinitsyna; A. V. Kochetov (Вавиловский журнал генетики и селекции)
Phytophthora infestans Mont. de Bary is the main oomycete pathogen of cultivated crops in the family Solanaceae, especially potato (Solanum tuberosum). Because potato is the fourth most cultivated crop worldwide, its annual losses from late blight are tremendous. Studies of the basic mechanisms of interaction between potato and the late blight pathogen not only expand the fundamental knowledge in this area, but also open up new possibilities for regulating these interactions in order to increase resistance to the pathogen. The interaction of potato and the late blight pathogen can be considered from a genetic point of view, and it is interesting to consider both the response of the potato to the colonization process by P. infestans and the change in gene activity in late blight during plant infection. We can also investigate this process by changing the profile of secondary metabolites of the host and the pathogen. In addition to fundamental work in this area, applied work in the form of the development of new preparations for protecting potatoes is of no less importance. This review briefly describes the main stages of studies of potato resistance to late blight, starting almost from the first works. Much attention is paid to key works on changing the profile of secondary metabolites phytoalexins. A separate section is devoted to the description of both qualitative and quantitative characteristics of potato resistance to the late blight pathogen: their contribution to overall resistance, gene mapping, and regulation capabilities. Both types of traits are important for potato breeding: quantitative resistance due to R-genes is quickly overcome by the pathogen, while quantitative trait loci make it possible to create varieties with almost absolute resistance due to the pyramid of effective genes. The latest approaches in molecular biology make it possible to study translatomic profiles, which makes it possible to look at the interaction of potatoes and the late blight pathogen at a different angle. It has been shown that the process of potato colonization affects not only the activity of various genes and the profile of secondary metabolites: proteinsmarkers of the response to infection from potatoes have also been identified: they are pathogen-bound proteins and plastid carbonic anhydrase. On the part of P. infestans, fungal cellulose synthase proteins and haustorium-specific membrane protein were markers of infection. Thus, the review contains information on the most relevant complex studies of the genetic mechanisms of potato resistance to late blight.